Development and validation of a novel sensitive UV-direct capillary electrophoresis method for quantification of alendronate in release studies from biomaterials - Cattalini, Juan Pablo (2017)
A simple, highly sensitive, and robust CE method applied to the determination of alendronate (ALN) was developed from matrices for tissue engineering, characterized by being highly complex systems. The novel method was based on the ALN derivatization with o-phthalaldehyde and 2-mercaptoethanol for direct ultraviolet detection at 254 nm. The BGE consisted of 20 mM sodium borate buffer at pH 10, and the electrophoretic parameters were optimized.The method was validated in terms of specificity, linearity, LOD, LOQ, precision, accuracy, and robustness. The LOD and LOQ obtained were 0.8 and 2.7 μg/mL, respectively. In addition, the method offers higher sensitivity and specificity compared to other CE and HPLC methods using UV-detectors, as well as low cost and simplicity that allowed the rapid and simple quantitation of ALN from bone regeneration matrices.